Estimation of Indonesia’s Fiscal Reaction Function - Pamungkas, Raditiyo Harya (Jurnal Kajian Ekonomi dan Keuangan, 2016)
Fiscal policy is a core factor in managing macroeconomic indicators strategy. Following several financial crises, both advanced and emerging countries undertook prudent fiscal policies to maintain debt sustainability. This paper investigates the fiscal policy behaviour of Indonesia through a fiscal reaction function, which represents how the government reacts to the debt to GDP ratio by the creation of primary balance in the budget. Breakpoint unit roottest is conducted due to the stationarity characteristics of data variables, hence the widely used Autoregressive Distributive Lag (ARDL) bound test is employed using quarterly data from 1990 to 2014. These results indicate that the government of Indonesia has reacted to the increase in debt to GDP bygenerating the primary surplus due to increase in debt accumulation which shows the well-behaved fiscal policy to maintain debt sustainability. In Indonesia’s fiscal reaction function, real interest rate, nominal exchange rateto US$, and election significantly determine the primary balance behaviour. In addition to maintaining a debt to GDP ratio at a low level, the government should also consider the other variables other than debt to achieve sustainability of fiscal policy especially in managing shocks.